2021
DOI: 10.14710/jil.19.3.620-629
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Prospektif Pengembangan Dalam Ekowisata Waduk Cirata Yang Berkelanjutan

Abstract: Pengembangan ekowisata waduk Cirata memiliki potensi besar dalam penggerak perekomian dan membangun kesejahteraan masyarakat tanpa harus mengorbankan sumber daya alam dan merusak lingkungan bahkan berkelanjutan.Pada studi ini, ini bertujuan untuk menentukan  variabel-variabel yang mempengaruhi pengembangan ekowisata di waduk Cirata serta mengetahui hubungan interdepensi antara variabel-variabel sehingga dapat dijadikan penentuan kebijakan dalam pengembangan ekowisata di waduk Cirata yang berkelanjutan. Metode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The analysis results found that the attributes in Quadrant III are output attributes characterized by minimal influences but very high dependence on influential variables. Attributes in this Quadrant are sensitive if there is a change in the variables in quadrants I and II [28], namely: input-output market access. Market access is essential regarding the availability of inputs and marketing of output products, namely livestock products.…”
Section: Results Of the Micmac Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis results found that the attributes in Quadrant III are output attributes characterized by minimal influences but very high dependence on influential variables. Attributes in this Quadrant are sensitive if there is a change in the variables in quadrants I and II [28], namely: input-output market access. Market access is essential regarding the availability of inputs and marketing of output products, namely livestock products.…”
Section: Results Of the Micmac Analysismentioning
confidence: 99%
“…Once sensitive attributes are known in RapDuck analysis, the next step is to group and determine the hierarchy of strategic variables using the MICMAC analysis (Cross Impact Matrix Multiplication Applied to Classification). This analysis is helpful for policy-making and avoids irrelevant variables resulting in failures [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bermanfaat sebagai sumber air baku PDAM Kabupaten Kuningan (Hermawati, 2015), objek wisata alam (Mauludin, 2017) dan sebagai tempat budidaya ikan melalui sistim keramba jaring apung (KJA) (Heriyanto et al, 2018). Manfaat waduk lainnya seperti diungkapkan sebelumnya yaitu sebagai pengendali banjir (Li et al, 2014), sumber air minum, budidaya ikan (Hermawaty, 2015), pariwisata (Hindayani et al, 2021), dan sebagai habitat berbagai tumbuhan air (H. Wang et al, 2022) serta penyedia jasa ekosistem (Bekoe et al, 2021); (Pratama et al, 2018).…”
Section: Latar Belakangunclassified
“…Selanjutnya, serta faktorfaktor yang mempengaruhi nilai WTP dan beberapa variabel sosio-demografis mengunakan model regresi logistik (Durán-Román et al, 2021;Jurado-Rivas & Sánchez-Rivero, 2019Liu et al, 2019;Pedroso & Biu Kung'u, 2019;Ramli et al, 2017;Reynisdottir et al, 2008;Rodella et al, 2019). Hasil studi menjadi sebagai dasar dalam menentukan kebijakan dan strategi prospektif pengembangan wisata (Hindayani et al, 2021), optimalisasi pengelolaan wisata, peluang kelestarian dan konservasi serta perbaikan kualitas lingkungan, perlindungan jasa ekosistem lingkungan serta meningkatkan pelayanan sarana dan prasarana kegiatan wisata.…”
unclassified